Lean Six Sigma in higher education institutes: an Irish case study. Issue 4 (1st November 2019) - O'Reilly, Seamus J.; Healy, Joe; Murphy, Tom; Ó'Dubhghaill, Rónán
Abstract : Purpose: This paper aims to contribute to a developing literature on continuous improvement (CI), enabled by Lean Six Sigma (LSS), in higher education institutions (HEIs). It reports on the key learning points arising from the initial steps taken by an Irish university on its CI journey. Design/methodology/approach: A case study strategy was adopted following a participatory research approach. This approach supports reflexivity and also provides access to all relevant documentation and staff within the case university. Thematic analysis was supported by data reduction and display techniques. Findings: The introduction of a LSS approach rather than a reliance on lean alone introduced a structured methodology (DMAIC) that supported simplification of a number of administrative processes. A number of specific improvements were achieved including: Cycle time and cost reduction; customer or employee satisfaction; and rework and error reduction. The findings support the importance of the Readiness Factors as identified by Antony (2014), with particular insight into the role of senior and middle management, the impact of training and deployment of expertise. Research limitations/implications: This paper is based on an ongoing, longitudinal, empirical study of a single case study in Ireland. Originality/value: This paper tracks the development of CI in a HEI in a longitudinal manner and adds to the emerging the literature in this area. The paper evaluates the role of management at various levels, analyses the use of LSS tools and techniques and evaluated the role of training and capacity building. Implications for Management are shared including: design and role of training programmes, role of champions at various organisational levels, including key functional areas and sustaining momentum.